The global entrepreneurship index (GEINDEX) - Zoltán J. Ács; László Szerb (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
This paper constructs a Global Entrepreneurship Index (GEINDEX) that captures the contextual feature of entrepreneurship across countries. We find the relationship between entrepreneurship and economic development to be mildly S-shaped not U-shaped or L-shaped. Our findings suggest moving away from simple measures of entrepreneurship across countries illustrating a U-shaped or L-shaped relationship to more complex measures, which are positively related to economic development. Implications for public policy suggest that institutions need to be strengthened before entrepreneurial resource can be deployed to drive innovation.
Keywords: L26; O1; O3; 330; Entrepreneurship; Development; Stages of Growth; Globalization; Innovation; Index; Knowledge; Institutions; Unternehmer; Unternehmensgründung; Wirtschaftsindikator; Entwicklungsstufe; Institutionalismus; Innovation; Wissen; Globalisierung; Welt